The role of research in advertising - Barlow, Roger; McCall, Simon; First Light Video Publishing (Venice, CA : First Light Video Pub., 2000)
Experts in the field of advertising debate the opportunities and problems that arise when a "creative idea" for advertising a product is researched.
Panelists, Simon McCall, Roger Barlow.
Keywords: Advertising campaigns -- Evaluation; Advertising -- Research; Television advertising